2014
DOI: 10.1103/physreve.89.053024
|View full text |Cite
|
Sign up to set email alerts
|

Capillary filling dynamics of viscoelastic fluids

Abstract: We consider the filling of a capillary by a viscoelastic fluid described by the Phan-Thien-Tanner (PTT) constitutive behavior. By considering both vertical capillary filling and horizontal capillary filling, we demarcate the role played by gravity and fluid rheology towards long-time oscillations in the capillary penetration depth. We also consider the isothermal filling of the capillary for a closed channel and thus bring out the fundamental differences in the nature of capillary filling for PTT and Newtonian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 63 publications
2
34
0
Order By: Relevance
“…The findings advance our understanding of time periodic electrokinetic phenomena of viscoelastic fluids and provide (Nguyen et al 2013). Chakraborty and colleagues have theoretically studied transport of non-Newtonian fluid (inelastic power law fluids and recently viscoelastic constitutions) using separately steady PDF (Bandopadhyay and Chakraborty 2011), steady EOF (Chakraborty 2007;Ghosh and Chakraborty 2015), time periodic PDF (Bandopadhyay and Chakraborty 2012a, b;Bandopadhyay et al 2014) and time periodic EOF (Bandopadhyay et al 2013) in rectangular narrow confinements. Afonso et al studied the combined steady PDF and EOF using two different viscoelastic fluid models, namely the Phan-Thien-Tanner (PTT) model and the finitely extensible nonlinear elastic with a Peterlin approximation (FENE-P) model (Afonso et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The findings advance our understanding of time periodic electrokinetic phenomena of viscoelastic fluids and provide (Nguyen et al 2013). Chakraborty and colleagues have theoretically studied transport of non-Newtonian fluid (inelastic power law fluids and recently viscoelastic constitutions) using separately steady PDF (Bandopadhyay and Chakraborty 2011), steady EOF (Chakraborty 2007;Ghosh and Chakraborty 2015), time periodic PDF (Bandopadhyay and Chakraborty 2012a, b;Bandopadhyay et al 2014) and time periodic EOF (Bandopadhyay et al 2013) in rectangular narrow confinements. Afonso et al studied the combined steady PDF and EOF using two different viscoelastic fluid models, namely the Phan-Thien-Tanner (PTT) model and the finitely extensible nonlinear elastic with a Peterlin approximation (FENE-P) model (Afonso et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…25 In recent studies, different aspects of contact line motion, like relevant scales, different regimes, dynamical transitions, and their influence over the capillary filing dynamics, have been discussed comprehensively. [26][27][28] Of late, electrically actuated flows through narrow confinements have gained prominence primarily due to its wide spectrum of important applications. [29][30][31][32][33][34][35][36] Such flows may come about by the movement of a charged layer of fluid (also known as Electric Double layer or, EDL) adjacent to a solid surface in presence of an external electric field.…”
Section: Introductionmentioning
confidence: 99%
“…The increase in viscosity using molecular fluids resulted in faster development from inertia to the pure viscous regime. Furthermore, it was found that the fluid requires less time to reach the maximum viscous force as the channel height increased which is similar to the capillary filling dynamics of viscoelastic fluids [30]. Lastly, the behavior of front position length was mostly affected by the spin viscosity in the third viscous-dominated region.…”
Section: Discussionmentioning
confidence: 82%
“…(13) by integrating it twice with zero boundary condition as [30]: (14) In the next section, different regimes for the capillary filling dynamics will be discussed.…”
Section: Mathematical Formulationmentioning
confidence: 99%